Metacognitive Awareness as a Predictor of Mathematics Problem-Solving Skills Among BSEd Mathematics Students - Dia Largo; Mary Maraña; Netchie Tandog; MARK LAURENTE (Journal of Digital Learning and Education, 2025)
This study aimed to determine the significant relationship between metacognitive awareness in terms of planning, monitoring, and evaluation, and mathematics problem-solving skills in terms of Polya’s four steps in problem-solving: understanding the problem, devising a plan, implementing a plan, and re-evaluation among BSEd Mathematics students in Davao de Oro State College, A.Y. 2022-2023. Utilizing a non-experimental quantitative design with a predictive correlational approach, the researchers surveyed students across all year levels using the Metacognitive Awareness Inventory (MAI) and the Problem-Solving Test Questionnaire (PSTQ) to gather data on their metacognitive awareness and problem-solving skills. Data analysis involved descriptive statistics and Kendall’s Tau Correlation, given the ordinal and continuous nature of the variables. Results indicated that students exhibited high metacognitive awareness and very high problem-solving skills. However, the study found no significant relationship between the two, as evidenced by a p-value of 0.566 (greater than 0.05) and a Kendall’s Tau correlation coefficient of 0.046. This signifies that the BSEd Mathematics students’ level of problem-solving skills is not affected or associated with the extent of their metacognitive awareness. This indicates that the students’ problem-solving skills are not influenced by their metacognitive awareness. The unexpected nature of this finding highlights the need for further research to understand the factors contributing to the lack of a significant relationship between these variables.